Electrocatalytic detection of biomarkers of tuberculosis and cervical cancer - Peteni, Siwaphiwe (University of the Witwatersrand, Johannesburg, 2024)
The need for simpler, low cost and efficient diagnostic methods remains a matter of urgency. This has opened numerous streams of research. Electrochemistry is a simple, cost effective and efficient method that has been used for the detection of several diseases such as tuberculosis (TB) and human papilloma virus (HPV). TB has been ranked amongst the most problematic diseases in HIV/AIDS burdened communities, this alone calls for concern. Biomarkers of TB not only indicate mycobacterium infection but can also assist in the early detection of TB which is highly beneficial for the infected person and the health care system. HPV is the causative agent for cervical cancer. Cervical cancer is ranked as the fourth disease that causes mortality amongst women. With that in mind, HPV-16 L1 early detecting means possible early detection of cervical cancer. In this thesis, methyl nicotinate (MN), which is one of TB’s biomarkers was detected in phosphate buffer solution (PBS, pH 6.0) and commercial human serum using cobalt nanoparticles supported on carbon derived from trimesic acid (TMA) (abbreviated as Co-NPs@CTMA) and biphenyldicarboxylic acid (BPDC) abbreviated as Co-NPs@CBPDC) as electrocatalysts. These electrocatalysts were obtained using microwave-assisted metal-organic framework process with TMA and BPDC as ligands. XRD data showed that these electrocatalysts are cobalt nanoparticles with dominant {111} and {200} phase with traces of cobalt oxide (CoO). XPS and Raman data showed that Co-NPs@CBPDC is defect-rich compared to the Co-NPs@CTMA counterpart. BET showed that CoPs@CBPDC has higher surface area and pore size and volume than the Co-NPs@CTMA catalyst. Both electrocatalysts showed reversible cobalt nanoparticle oxidation and reduction reactions, in the absence and in the presence of the MN, thereby allowing for a facile indirect electrochemical detection of this biomarker. The calibration curves showed low limit of detection (LoD) of 0.47 and 0.147 µM for Co-NPs@CTMA and Co-NPs@CBPDC, respectively. The higher performance of the latter is attributed to its enhanced physico-chemical properties compared to the former. Next, HPV-16 L1, which is the conventional high-risk antigen that is present in cervical cancer, was detected using onion-like carbon (OLC) and polyacrylonitrile fibre integrated with OLC (OLC-PAN) as electrode platforms. Two electrode platforms were used; onion-like carbon (OLC) and its polyacrylonitrile (OLC-PAN) composites. Both platforms led to the detection in a wide linear concentration range (1.95 fg/ml to 50 µg/ml), excellent sensitivity (>5.2 µA/log([HPV-16 L1, fg/mL]) and ultra-low detection of ca. 1.0 and 1.4 fg/ml for OLC-PAN and OLC-based immunosensors, respectively. The high specificity of detection was proven by experimenting with an anti-Ovalbumin antibody (anti-Ova) and native Ovalbumin protein (Ova). An immobilized antigenic HPV-16-L1 peptide showed insignificant interaction with anti-OVA in contrast with the excellent interaction with anti-HPV-16 LI antibody. The immunosensors showed satisfactory stability of ~ 3 days of re-usability. The application of the immunosensor as a potential point-of-care diagnostic (PoC) device was investigated with the screen printed carbon electrode which showed the ability to detect ultra-low (~ 0.7 fg/ml) and high (~ 12 µg/ml) concentrations. This study opens the door of opportunity for further investigation with other electrode platforms and realization of PoC diagnostic devicesfor screening and testing of HPV biomarker for cervical cancer.
A thesis submitted in fulfilment of the requirements for the degree of Doctor of philosophy in Chemistry, to the Faculty of Science, School of Chemistry, University of the Witwatersrand, Johannesburg, 2024.
Keywords: Biomarkers; Tuberculosis; Methyl nicotinate; Metal organic framework; Human pappilloma virus; HPV 16 L1; Onion like carbon; polyacrylonitrile fibers; electrochemical detection; UCTD; SDG-9: Industry, innovation and infrastructure; SDG-3: Good health and well-being